Implementing clinical guidelines in the treatment of hypertension in general practice: evaluation of patient outcome related to implementation of a computer-based clinical decision support system. - Hetlevik I; Holmen J; Krüger Ø (Scandinavian Journal of Primary Health Care, 1999)
OBJECTIVE: To evaluate the implementation of clinical guidelines for hypertension in general practice by use of a computer-based clinical decision support system (CDSS) and a specific implementation strategy. Evaluation of patient outcome. DESIGN: Randomised study with health centres as units. The intervention group had the CDSS installed and made ready for use, doctors and assistants were trained and received a user-manual, the doctors were offered telephone repetitions, a seminar in risk intervention and, at the same seminar, further demonstration of the CDSS. The doctors received baseline registrations with information of how they treated their own hypertensive patients, and use of the CDSS was checked repeatedly. SETTING: General practice in Sor- and Nord-Trondelag counties in Norway, 380,000 inhabitants. PARTICIPANTS: Seventeen health centres with 24 doctors and 984 patients in the intervention group. Data from 879 patients used in the final analyses. Twelve health centres with 29 doctors and 1255 patients in the control group. Data from 1119 patients used in the final analyses. MAIN OUTCOME MEASURES: After an intervention period of 18 months, group differences in level of systolic and diastolic blood pressure, serum cholesterol, body mass index, and risk score for myocardial infarction were calculated, as well as group differences in fractions of smokers. RESULTS: Significant group difference in favour of intervention group: diastolic blood pressure 1 mmHg (95% CI -1.89, -0.17). However, a significant baseline difference in systolic blood pressure in favour of control group of 2.7 mmHg (95% CI 1.0, 4.5) had been reduced to 1.2 mmHg (95% CI -0.6, 3.0) after intervention. CONCLUSION: Implementation of clinical guidelines in the treatment of hypertensive patients in general practice by means of a CDSS and several other procedures for implementation did not affect patient outcome in any clinically significant way.